Performance Analysis of Logic Gate-Based Power Amplifier Protection with Hybrid Filtering - gaguk firasanto; Andriani Andriani; Kiswanta Kiswanta (PROtek : Jurnal Ilmiah Teknik Elektro, 2026)
Class-D audio power amplifiers deliver high operational efficiency but remain highly susceptible to catastrophic failures induced by thermal runaway and overcurrent events. Conventional protection mechanisms, such as passive fuses, typically exhibit delayed response times and lack the capability to record historical diagnostic data. This study designs and implements an active, intelligent protection framework driven by an Arduino Nano microcontroller and a Python-based interface. The methodology integrates an LM35 thermal sensor and an INA219 digital current monitor, strictly validated through a one-point calibration procedure and enhanced by a hybrid filtering technique to eliminate signal noise. A digital OR logic gate algorithm is applied to execute rapid decision-making. Experimental results demonstrate exceptional measurement precision, achieving an average relative error of only 0.43% for temperature and 1.16% for current. The logic-based actuator successfully and instantaneously disconnected the power load during simulated fault conditions whenever the predefined safety thresholds (60°C or 2.0 A) were exceeded. Furthermore, the integrated data logger effectively captured real-time failure telemetry for post-incident evaluation. In conclusion, the proposed digital logic framework provides a highly responsive, data-driven, and superior preventive alternative to traditional passive audio amplifier protection.